Antioxidant Activity Using DPPH & Frap Method and Their Correlation with The Levels of Phenolic and Flavonoid Compounds from Nemba Plants (Azadirachta Indica A. Juss) - Haryoto Saroyo; Ismi Aziz Nur Arifah (Universitas Muhammadiyah Surakarta, 2020)
One of the herbal plants, namely neem (Azadirachtaindica A. Juss) can generally be used as an ingredient for traditional medicine. Neem is known to have the potential to produce antioxidants, where it can play an important role in counteracting free radicals. As a result of the increasing number of free radicals, the number of antioxidants and free radicals becomes unbalanced. If this continues, it can cause problems, namely the emergence of various kinds of serious diseases. The purpose of this literature review is to present articles related to the potential for antioxidant activity; content of phenolic compounds and flavonoids; knowing whether there is a relationship between phenolic compounds and flavonoids on antioxidant activity; as well as providing information related to other potentials of neem (Azadirachta indica A. Juss) plants. Several studies have stated that the neem plant has antioxidant activity. The strongest antioxidant activity was found in the neem root. The secondary metabolites produced are alkaloids, flavonoids, steroids, polyphenols, glycosides, phenols, tannins, essential oils, carotenoids, fatty acids, and saponins. Another study also stated that neem has the potential for other pharmacological activities such as antibacterial, immunomodulatory, antidiarrheal, and antifungal activities. polyphenols, glycosides, phenols, tannins, essential oils, carotenoids, fatty acids, and saponins. Another study also stated that neem has the potential for other pharmacological activities such as antibacterial, immunomodulatory, antidiarrheal, and antifungal activities. polyphenols, glycosides, phenols, tannins, essential oils, carotenoids, fatty acids, and saponins. Another study also stated that neem has the potential for other pharmacological activities such as antibacterial, immunomodulatory, antidiarrheal, and antifungal activities.